PROSES PEMECAHAN MASALAH MATEMATKA SISWA BERKEMAMPUAN TINGGI BERDASARKAN LANGKAH POLYA - lalu saparwadi; Cahyowatin Cahyowatin (Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this study is to determine the process of solving the problem of students who are high-ability based on Polya step. This research uses the qualitative approach. The subject in this study was a high-ability student. The results of this study indicate that the ability to solve the problem of high-ability students based on Polya steps are: (1) Understanding the problem begins by understanding the vocabulary, identifying all the facts in the form of existing information data, connecting all information from the identification result, and ending by identifying the question ; (2) A plan for splitting begins with the selection of operations and establishes the formulation of equations; (3) Implement the plan of splitting; (4) Re-checking of the settlement result obtained by substituting the result obtained to the initial equation.